2020
DOI: 10.3390/ijms21051786
|View full text |Cite
|
Sign up to set email alerts
|

Using Serum Amino Acids to Predict Traumatic Brain Injury: A Systematic Approach to Utilize Multiple Biomarkers

Abstract: Traumatic brain injury (TBI) can cause biochemical and metabolomic alterations in the brain tissue and serum. These alterations can be used for diagnosis and prognosis of TBI. Here, the serum concentrations of seventeen amino acids (AA) were studied for their potential utility as biomarkers of TBI. Twenty-five female, 4-week-old piglets received diffuse (n = 13) or focal (n = 12) TBI. Blood samples were obtained both pre-injury and at either 24-h or 4-days post-TBI. To find a robust panel of biomarkers, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Serum NAA also showed significant changes following blast exposure. As a highly abundant metabolite in brain tissue, decreased levels of NAA have been reported in the brain following blunt-force brain injury using MRS, suggesting potential leakage into the bloodstream [ 39 ]. The increased serum levels observed in the current study provide supporting evidence of NAA leakage into the bloodstream following brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Serum NAA also showed significant changes following blast exposure. As a highly abundant metabolite in brain tissue, decreased levels of NAA have been reported in the brain following blunt-force brain injury using MRS, suggesting potential leakage into the bloodstream [ 39 ]. The increased serum levels observed in the current study provide supporting evidence of NAA leakage into the bloodstream following brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Among the specific amino acids undergoing a decline in previous studies were alanine (Deutschman, 1987), arginine (Flakoll et al, 1995Petersen et al, 1996), glutamine (Deutschman, 1987;Flakoll et al, 1995;Petersen et al, 1996;Yi et al, 2016), proline (Flakoll et al, 1995Louin et al, 2007;Zheng et al, 2017), serine (Flakoll et al, 1995;Yi et al, 2016;Hajiaghamemar et al, 2020), taurine (Flakoll et al, 1995;Hajiaghamemar et al, 2020), threonine (Flakoll et al, 1995;Zheng et al, 2017), tryptophan (Flakoll et al, 1995Taraskina et al, 2022), and the branched-chain amino acids (BAA) leucine, isoleucine, and valine (Vuille-Dit-Bille et al, 2012;Jeter et al, 2013). On the other hand, a small number of other studies have also shown a mixed pattern of increased and decreased plasma amino acids, both in human TBI (Deutschman, 1987;Flakoll et al, 1995;Vuille-Dit-Bille et al, 2012) and animal models (Hajiaghamemar et al, 2020). The amino acids most consistently found to be elevated in these studies were the BAAs and phenylalanine (Deutschman, 1987;Flakoll et al, 1995), which is consistent with our present results.…”
Section: Amino Acids In Traumatic Brain Injurymentioning
confidence: 98%
“…There have been conflicting results from previous studies on this topic; some studies reported subacute "nitrogen loss" (Flakoll et al, 1995), namely a general decrease in the plasma levels of the majority of the amino acids in humans (Flakoll et al, 1995;Petersen et al, 1996;Yi et al, 2016) and in animal models of TBI (Louin et al, 2007;Zheng et al, 2017;Taraskina et al, 2022). Among the specific amino acids undergoing a decline in previous studies were alanine (Deutschman, 1987), arginine (Flakoll et al, 1995Petersen et al, 1996), glutamine (Deutschman, 1987;Flakoll et al, 1995;Petersen et al, 1996;Yi et al, 2016), proline (Flakoll et al, 1995Louin et al, 2007;Zheng et al, 2017), serine (Flakoll et al, 1995;Yi et al, 2016;Hajiaghamemar et al, 2020), taurine (Flakoll et al, 1995;Hajiaghamemar et al, 2020), threonine (Flakoll et al, 1995;Zheng et al, 2017), tryptophan (Flakoll et al, 1995Taraskina et al, 2022), and the branched-chain amino acids (BAA) leucine, isoleucine, and valine (Vuille-Dit-Bille et al, 2012;Jeter et al, 2013). On the other hand, a small number of other studies have also shown a mixed pattern of increased and decreased plasma amino acids, both in human TBI (Deutschman, 1987;Flakoll et al, 1995;Vuille-Dit-Bille et al, 2012) and animal models (Hajiaghamemar et al, 2020).…”
Section: Amino Acids In Traumatic Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomic biomarkers are currently being widely explored for TBI. 89,[98][99][100][101][102][103][104][105][106][107] Because no single metabolite has yet been identified with sufficient diagnostic power, most reports focus on metabolite panels that explain a significant amount of the variance observed between TBI patients/models (typically controlled cortical impact, fluid percussion, and weight-drop models) and controls (typically healthy individuals or "sham" craniotomy models). 108 A selection of metabolites reported with altered levels in TBI is shown in Table 1.…”
Section: Metabolomic Biomarkersmentioning
confidence: 99%